Global financial regulation: shortcomings and reform options - Jones, E; Knaack, P (Wiley, 2019)
Standard‐setting bodies in global finance follow a core‐periphery logic, imposing a rigid dichotomy between standard‐setters and standard‐takers. They also focus exclusively on promoting financial stability. We argue that both attributes are increasingly problematic in today's world of globalised finance. Developing countries outside of standard‐setting bodies are highly integrated into global finance and while they are not systemically important, they are greatly affected by the regulatory decisions taken in the core. Analysing Basel banking standards, we show how the two‐tier structure of decision‐making results in international standards that generate adverse implications for countries in the periphery, particularly developing countries. Focusing on debates over the regulation of non‐bank credit intermediation, we show how the exclusive focus on financial stability can operate to the detriment of other important policy objectives, including financial inclusion. To improve the efficacy of international standard setting we make a series of recommendations aimed at increasing the applicability of standards to a wide variety of jurisdictions, and widening the focus of standard‐setting beyond financial stability. We also propose the creation of a new standard‐setting body for the regulation of fintech that models a more inclusive and holistic approach.